POLITENESS STRATEGIES PERFORMED BY THE HOST OF KICK ANDY SHOW “BERPRESTASI DI USIA MUDA” EPISODE - DEWI, ANJASMORO (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: politeness strategies, positive politeness, negative politeness Human beings have interaction process in their communication, and itactually makes the role of language in human’s daily life very important. Using a language, we can communicate and express our ideas or wishes to other people. One of strategies which used in communication is politeness. This study aims at answering the following two problems of the story: (1) What are the politeness strategies performed by the host of Kick Andy Show “Berprestasi di Usia Muda” episode? and (2) What are the potential reasons of the host in using the politeness strategies in Kick Andy Show ”Berprestasi di usia Muda” episode? This study uses qualitative approach. The data source is the trancript of theutterance produced by the host of Kick Andy Show “Berprestasi di Usia Muda”episode. In this study, the writer used document analysis because the dataanalyzed are the host’s utterances containing politeness strategies in Kick AndyShow “Berprestasi di Usia Muda” episode.It was found out that most of the time Andy as the host performed positivepoliteness when he delivered his utterances in order to minimize the distance with the guests. From the analysis result and discussion, the writer found out that there are 97 politeness strategies applied by Andy in Kick Andy Show.The elaboration is 20 for negative politeness with the percentage of (21%) and 77 positive politenesss strategies with percentage of (79%). Those results indicate that Andy applied more positive politeness strategies than other negative politeness strategies. The potential reason of using positive politeness strategies is to show Andy’s closeness, solidarity and seeking agreement with his guests. On other hand  negative politeness strategies to minimize the FTA with his guests. The writer suggest to other researchers  could analyze politeness strategiesin other media, such as speeches or debates performed by other figures. The next researcher could also use other theories in politeness strategies to enrich the knowledge for those reading his or her research report.